miR-3529-3p/ABCA1 axis regulates smooth muscle cell homeostasis by enhancing inflammation via JAK2/STAT3 pathway - Wang, Tingyu; Yu, You; Ding, Yinglong; Yang, Ziying; Jiang, Shumin; Gao, Faxiong; Liu, Shan; Shao, Lianbo; Shen, Zhenya (Frontiers in Cardiovascular Medicine, 2024)
Thoracic Aortic Dissection (TAD) is a life-threatening disease without effective drug treatments. The disruption of Human Aortic Smooth Muscle Cells (HASMCs) homeostasis is one direct histopathologic alteration in TAD pathological process.Several miRNAs have been shown abnormally expressed in TAD and to regulate HASMCs homeostasis. Bulk miRNA sequencing was performed to explore the aberrantly expressed miRNA profile in TAD, and the result showed miR-3529 was elevated in TAD tissues and confirmed by qRT-PCR. Further experimental assay revealed miR-3529 upregulation induced HASMCs homeostasis disruption, accompanied by reducing contractile markers and increasing pro-inflammatory cytokines. Integrative transcriptomics and metabolomics analysis were used to uncover the functional roles of miR-3529 in regulating HASMCs homeostasis. The data showed that miR-3529 overexpression altered the metabolic profile of HASMCs, particularly lipid metabolism. ABCA1 was found to be a direct target of miR-3529, which was verified through a dual-luciferase reporter assay. Mechanistically, the miR-3529/ABCA1 axis disrupted HASMCs homeostasis and promoted inflammatory responses through the JAK2/STAT3 signaling pathway. These findings favor a role for miR-3529 as a novel target for TAD therapy.